Ethnopharmacological analysis of medicinal plants in Jech Doab, Pakistan - Munawar, Tayyaba; Bibi, Yamin; Qureshi, Rahmatullah; Ahamad, Farooq; Sibtain Hussain; Abdul Qayyum (Ethnobotany Research and Applications, 2022)
Background: The main purpose of this study was to evaluate the aboriginal knowledge regarding use of medicinally important plant species from Tehsil Malakwal, District Mandi Bahauddin, Pakistan. Methodology: A total of 120 inhabitants (75women and 45 men) were interviewed for by using semi structured questionnaire. Data was analyzed qualitatively as well as by using quantitative indices of Relative Frequency of Citation (RFC), Use Value (UV), Fidelity Level (FL), Informant Consensus Factor (ICF) and Jaccard Index (JI). Results: A total of 60 medicinally important plant species belonging to 35 families were reported from study area. Plant diversity showed that Fabaceae (20%) was dominating family. Herb (55%) was leading life form of plants and leaves (31.03%) showed maximum usage for medicinal purpose. Decoction (20.92%) was most common mode of utilization. RFC and UV ranged from 0.16-0.90 and 0.02 to 1, respectively. 9 plant species showed 100% fidelity level. The highest ICF value was recorded for gastrointestinal disorders (0.96). The value of Jaccard Index ranged from 0.54 to 28.24%. Some of medicinal plants showed new medicinal uses not reported in previous studies. Conclusion: Study concludes that local inhabitants still prefer medicinal plants over allopathic medicine for treating various ailments. But this precious knowledge is restricted to old age people. So, awareness is necessary to conserve this knowledge. Keywords: Ethnomedicine, Malakwal, Mandi Bahauddin, Indigenous people, Medicinal plants